Molecular mediators of the cardiacbenefits of exercise - Khetarpal, Sumeet A.; Li, Haobo; Lerchenmüller, Carolin; Rhee, James; Rosenzweig, Anthony (Circulation research, 2025)
Exercise exerts myriad cardiovascular benefits and protects against most forms of cardiovascular disease. While extensive epidemiological evidence supports the clinical benefits of exercise, our understanding of the molecular underpinnings of its benefits in the heart remains incomplete. Pinpointing these mechanisms is essential to identifying molecular targets modulated by exercise for therapeutic gain. In this review, we discuss the cellular and molecular mechanisms through which exercise benefits the heart, with a focus on the cardiomyocyte. We highlight cardiomyocyte-secreted mediators of intercell communication, intracellular signaling pathways, transcriptional regulation, and posttranscriptional mechanisms through noncoding RNAs that have been implicated in the cardiac exercise response. We emphasize pathways and mediators regulated by exercise training that may provide therapeutic targets in heart failure.
Online veröffentlicht: 3. Juli 2025
Gesehen am 05.11.2025